Synthesis of PANI/Iron (II, III) oxide hybrid nanocomposites using SolGel method - Hussain, Nurul Husna Izzatti; Mustafa, Mohd Kamarulzaki; Asman, Saliza (UTHM Publisher, 2018)
A polyaniline/iron (II,III) (PANI/Fe₃O₄) hybrid nanocomposites were synthesized using a sol-gel method. The characterization of PANI/Fe₃O₄ hybrid nanocomposites were studied by Fourier transforms infrared spectroscopy with attenuated total reflectance (FTIR-ATR), multimeter, and permanent magnet. The FTIR result indicated that the PANI/Fe₃O₄ hybrid nanocomposites were successfully synthesized due to the chemical interaction was occurred by comparing a spectra of Fe₃O₄, polyaniline (PANI) and PANI/Fe₃O₄ hybrid nanocomposites. The electrical conductivity and magnetic properties of PANI/Fe₃O₄ hybrid nanocomposites were clearly performed using a multimeter and a permanent magnet, respectively. Application of external field to the sample have resulted 0.1 mV and 0.001 V DC readings for conductivity. While a Fe₃O₄ in the hybrid nanocomposites shows attractions to the permanent magnet, thus producing a magnetic field.